Hubungan Pengetahuan Ibu Dengan Pemberian MP-ASI Dini Pada Bayi Usia 0-6 Bulan Di Klinik Aminah Amin Rianta I Samarinda - Khotimah Nur Siam; Jasmawati; Lukman Nulhakim (Stikes Muhammadiyah Klaten, 2023)
MP-ASI (ASI Complementary Foods) is the provision of complementary foods other than breast milk when the baby is 6 months old because breast milk alone only provides half of the nutritional needs of babies at the age of 6-12 months. Data from the World Health Organization (WHO) in 2016 still shows that the average rate of exclusive breastfeeding in the world is only around 38%. The type of research is a descriptive analytical survey with a cross sectional design. Sampling used purposive sampling technique, then sample data was obtained through a questionnaire. Data analysis using Pearson Chi Square test. with p-value < (0.05), it is said that there is a relationship between the independent variable and the dependent variable. There is a relationship between maternal knowledge level and early complementary feeding at Aminah Amin Rianta 1 Samarinda Clinic, which can be seen from the value of p = 0.000 < = 0.05, which means H0 is rejected.